2022
DOI: 10.1177/03635465221096672
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Assessment of Hamstring Graft Healing and Integration 1 and Minimum 2 Years after ACL Reconstruction

Abstract: Background: An increase has been seen in the number of studies of anterior cruciate ligament reconstruction (ACLR) that use magnetic resonance imaging (MRI) as an outcome measure and proxy for healing and integration of the reconstruction graft. Despite this, the MRI appearance of a steady-state graft and how long it takes to achieve such an appearance have not yet been established. Purpose: To establish whether a hamstring tendon autograft for ACLR changes in appearance on MRI scans between 1 and 2 years and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In an MRI study of 250 patients, a 1-point increase in the SIR was associated with a 40% increase in the risk of graft failure. In an MRI study at 1 and 2 years, Putnis et al 44 found no major change in the SIR. This suggests that the ligamentization process mainly occurs during the first year and that it is directly related to the risk of the graft failing.…”
Section: Discussionmentioning
confidence: 93%
“…In an MRI study of 250 patients, a 1-point increase in the SIR was associated with a 40% increase in the risk of graft failure. In an MRI study at 1 and 2 years, Putnis et al 44 found no major change in the SIR. This suggests that the ligamentization process mainly occurs during the first year and that it is directly related to the risk of the graft failing.…”
Section: Discussionmentioning
confidence: 93%
“…29 Naraoka et al 20 demonstrated that there was no association between tunnel enlargement and graft integration grade. In contrast, Putnis et al 23 showed that tunnel contraction was positively correlated with graft signal intensity, and they reported that this could be a useful indicator of graft integration. In the present study, a similar correlation was found between graft tunnel volume and intratunnel graft SNQ as well as integration grade in the tibial tunnel.…”
Section: Discussionmentioning
confidence: 92%
“…MRI evaluation of the integration of the graft should also be considered [30][31][32]. Although the development of surgical techniques and improved rehabilitation protocols have been remarkable, the repercussions of an ACL injury are still significant.…”
Section: Discussionmentioning
confidence: 99%